If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1 = x + 39 Reorder the terms: -1 + 5x = x + 39 Reorder the terms: -1 + 5x = 39 + x Solving -1 + 5x = 39 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1 + 5x + -1x = 39 + x + -1x Combine like terms: 5x + -1x = 4x -1 + 4x = 39 + x + -1x Combine like terms: x + -1x = 0 -1 + 4x = 39 + 0 -1 + 4x = 39 Add '1' to each side of the equation. -1 + 1 + 4x = 39 + 1 Combine like terms: -1 + 1 = 0 0 + 4x = 39 + 1 4x = 39 + 1 Combine like terms: 39 + 1 = 40 4x = 40 Divide each side by '4'. x = 10 Simplifying x = 10
| y^2-y/2-1/5=0 | | -1/5×2/9= | | 16m^4-25n^2= | | 2(2)+y=-6 | | 2(1)+y=-6 | | 11x-5(2x+3)=-14 | | 2(0)+y=-6 | | 2e^5x=1572 | | x^4-12x^3+45x^2-54x-9sqrt(2)-2=0 | | 3x+5(3x-5)=11 | | 10(g+5)=2g+9 | | 5x-2(x-3)=18 | | 13.9p-19.99=7.61+15.4p | | (x^2-3x-4)-(x^2+3x-7)= | | 2x(x-8)=x+3x-5 | | 7j-20=6j-11 | | 2x+3(x+2)=-19 | | x=-x^2+2x+4 | | -18-13-18k=-15k+20 | | k^2+3k-4=0 | | 2(x-8)=x+3x-5 | | 1.5x+x=9 | | 8x^3+2x-2=7x^3+2x-10 | | 6i^2+17i+23=0 | | -16+2q=4q | | (x^2)(x^2)= | | 1x-15r= | | -9(x+3)+4x+5=8x+12 | | 2/3×-15r= | | 32=x^2-1 | | f(x)=9x^2-4 | | (x^2+3)(x^2+4x-3)= |